Tennis-Ball Collecting Robot - Sultan, Majdi; Abu Omar, Sohaib; Sharabati, Mahmoud (Palestine Polytechnic University (PPU) - mechatronics, 2018)
Abstract Tennisis aracket sportplayed on a rectangular and flat surface court. It can be playedindividually against a single opponent (singles) or between two teams of two players each (doubles). Modern tennis balls are made of hollowvulcanized rubberwith afeltcoating witha diameter of 65.41 to 68.58mm and a weight of 56 to 59.4gram. Tennis players need to collect the played balls from different locations in the court. Intraining sessions many balls are used and played. This makes the collection a tedious and tiringprocess. Some tools and mechanisms are used to facilitate the collection process such as pickup hoppers and tubes. In this graduation project, we designed and built a nouvelle autonomous / semi-autonomous mobile robot to specifically collect up to fifty tennis balls. The robot navigatesthrough two independently-actuated wheels and is stabilized by a castor. The nouvellecollection mechanism is based on a spinning brush that pushes tennis balls into a lightweightbasket on top of the robot.A motor makes the drum spins at a desired speed that isexperimentally verified. Three successive working prototypes have been designed, built, andtested to make sure the adopted ideas and conceptual designs are applicable and robust. The mobile robothas its own on-board intelligence where it is equipped with a camera,sonars, and a myRIO embedded device. The robot can identify, localize, and collect tennis ballsautonomously or, alternatively, a tennis player can command the robot to move it and collectthe balls through a mobile-phone application. [In the future, global cameras and a centralimage-processing system will be used for identifying and localizing all tennis balls on the court.This system is thought as well to take care of optimal path planning, collision avoidance, andmobile robot navigation].
CD, no of pages 86, 1/2018ميكاترونيكس, in the store
Keywords: Tennis-Ball ,Collecting Robot